NILAI PENDIDIKAN RELIGIUS, TOLERANSI DAN GEMAR MEMBACA DALAM NOVEL AYAT-AYAT CINTA 2 - Gusti Alamsyah Afandi (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2016)
This study aims to determine the value of religious character education, tolerance, and love of reading in the novel Ayat-ayat Cinta 2 by Habiburrahman El Shirazy. Describing quotation data regarding religious character values, tolerance character values, and reading character values in the novel Ayat-ayat Cinta 2 by Habiburrahman El-Shirazy. Then analyzed and discussed in this study. This research uses a qualitative approach and the type of library research. The data technique uses documentation techniques. The data analysis technique used is content analysis. The results showed that: 1) The value of character education in the novel Ayat-ayat Cinta 2 by Habiburrahman El Shirazy regarding the value of religious character found 68 quotes divided into 10 categories, 5 quotes for tolerance character, and 8 quotes for characters who like reading. 2) The value of tolerance character education 5 quotes divided into 3 categories. 3) The reading character value is 8 quotes with 4 categories.